Pendidikan Karakter Perspektif Sayyid Muhammad dalam Kitab At-Tahliyah Wa At-Targhib Fi Atarbiyah Wa At-Tahdib - Rosyana Kusumaningrum; Bustanul Arifin (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
This study describes three concepts of Thomas Lickona's character education which are implemented with Sayyid Muhamad's thoughts in the book of tahliyah. This research seeks to answer how the concepts of knowing the good, desiring the good, and doing the good in the perspective of the book in our perspective are At-Tahliyah wa At-Targhib fi Atatarbiyah wa At-Tahdib. Data collection was carried out by researchers to obtain data about character education ideas contained in the book of Tahliyah using a descriptive qualitative analysis method with the type of literature review and using content analysis as a data analysis technique. The results of this study state that the characters that must be instilled in education include; first, honest, good manners, obey the rules, shyness, independence, and knowledge. Second, ukhwah, khusnul khuliqi as a way to get used to it. Third, sulukul insan as an indicator of doing the good